Universal peace$1 (Bfrom a woman's standpoints - Suttner, Bertha von, 1843-1914 (Salt Lake City, UT : Project Gutenberg, 2022)
"Universal Peace$1 (BFrom a Woman$1 (Bs Standpoint" by Baroness Bertha von Suttner is a philosophical treatise written in the late 19th century. The book passionately advocates for the cause of universal peace, challenging traditional views on war and promoting the influence of women in the peace movement. Written during a time of increasing militarization in Europe, it offers insights into the intersection of gender, ethics, and human progress. In the text, von Suttner critiques the glorification of war and argues that true progress requires the contributions of women to the peace discourse, transcending their roles as mere victims of war. She illustrates how societal evolution towards a more civilized state necessitates the abandonment of militarism and the establishment of justice through arbitration rather than conflict. The book discusses the significance of the Hague Peace Conferences and outlines von Suttner's vision of a future where mutual understanding and cooperation replace hostility and violence. Ultimately, she asserts that the path to universal peace is intertwined with the elevation of both genders, calling for a collective moral awakening to reject the horrors of war. (This is an automatically generated summary.)s
Release date is 2022-11-29
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Peace; Pacifism; Peace movements